A case report of postpartum acute aortic dissection - Adineh Taherkhani; Maryam Taherkhani (International Journal of Cardiovascular Practice)
Acute aortic dissection is a rare but lethal disaster during pregnancy and early postpartum. It has a very high mortality. Emergent or urgent surgical correction is the preferred treatment for the most patients. We report a case of postpartum type A aortic dissection who underwent successful emergent Bental procedure.